Robotic Urologic Surgery - Dasgupta, Prokar (Springer, 2017)
Robotics is one of the hottest topics in medicine today, with an international interest that is exponentially growing. The introduction of robotic technology into modern operating theatres has provoked a revolutionary change in the basic surgical approach, with many advantages over traditional open surgical treatment, including faster recovery and a significantly lower risk of surgical trauma. Furthermore, robotic technology has already also surpassed the traditional laparoscopic approach by providing full three-dimensional vision, intuitive motion and wristed instrumentation with motion scaling (...)